The Effect of Improved Water, Sanitation and Hygiene on Linear Growth Amongst Children Living in Developing Countries: A Systematic Review - Elton Chavura; Wales Singini; Russel Chidya; Balwani Chingatichifwe Mbakaya (European Scientific Journal, ESJ, 2022)
Constant exposure to poor water, sanitation and hygiene (WaSH) contribute to environmental enteric dysfunction; a disorder that is frequently implicated as a cause of linear growth failure. We aimed to evaluate the efficacy of WaSH on linear growth amongst children aged 0-59 months. We reviewed fourteen (14) studies retrieved from AMED, CINAHL, DOAJ, PubMed, PsycINFO, Google Scholar, and EMBASE databases following guidelines developed by PROSPERO and COCHRANE. The screening process was summarized using a PRISMA flow diagram, and the methodologies were critically appraised by a Mixed Method Appraisal Tool. The following search terms were employed in the search strategy: sanitation and/or improved water supply and/or WaSH and/or stunting and/or linear growth and/or environmental enteric dysfunction. No difference was seen in mean height for age Z-score (0.01, 95% CI-0.16 to 0.18) between children who received WaSH interventions and those who did not. Only five (5) studies reported a significant association between WaSH and child linear growth (P < 0.001). All combination intervention studies included in this review did not establish any significant benefit of WaSH and nutrition integration, presumably due to methodological limitations and a short duration of exposure to the interventions. Although robust sanitation coverage could be an important component amongst proven interventions to stimulate linear growth, stunted growth is embedded within myriad determinants beyond improved WaSH. More research is needed to quantify the complementary effect of WaSH and nutrition co-programming. This systematic review was registered in the PROSPERO database with registration number CRD42022322462.